A reconstrução identitária e de pertencimento nos processos migratórios: haitianos em escola pública do município de Marau/RS - Brizola, Natália Fioravanso Vieira (2021)
Migration processes, although always present in the history of humanity, became significantly evident in modern societies at the end of the 20th century and beginning of the 21st century as one of the consequences of globalization. Among the immigrants are their children, the second generation of them, inserted in educational spaces, requiring educators and institutions, as well as the entire school community, to review and readapt educational and inclusive practices. For many, school represents the first place outside the family environment where they will have contact with differences, and for this reason, the exercise of otherness, integrative processes and cultural exchanges is essential. It is not uncommon for the tensions of society, issues pertinent to interpersonal relationships, and conflicts of identity and culture to converge in school. Given this reality, this research aims to analyze processes involving Haitian immigration to Brazil since 2010, particularly to the Northeast region of Rio Grande do Sul, with the municipality of Marau as the epicenter due to the presence of work spaces in agro-industrial horizons; seeks to address their motivations, insertion into the job market and, fundamentally, the children, sons and daughters of Haitian immigrants in institutional educational spaces; understand how belonging to the destination society occurs, the consequent reconstruction of identity and adaptation of both parties involved in the process. The questioning of this study is an attempt to understand how relationships, moments, and situations of co-presence of immigrants in schools are produced, as well as the cultural and social processes that result from them. To do this, a literature review was conducted on Haiti; Haitian emigration to various parts of the world, especially to Brazil; aspects of the international migration phenomenon, generally from the last decades; and, above all, interviews with parents and students of Haitian immigrants in the municipality of Marau, teachers from schools where immigrant students are enrolled, photographic records, reports, and observation of the behavior of these students in the school environment, their arrival and their adaptation to the new country. The conclusive ideas revolve around the search of these immigrants for insertion and belonging in society - the second generation, through education and coexistence in educational spaces; and adult immigrants, seeking to conquer their space through work and their social structure, as well as their families. Based on the research carried out, it was possible to understand how the process of adaptation of these immigrants in the destination society takes place and the aforementioned insertion and belonging in the school environment, through integralizing pedagogical practices and actions that aim at the development of values ​​such as otherness, autonomy and protagonism. It was also possible to perceive the receiving society from the perspective of the immigrant and how it can modify its pre-established values ​​and culture in favor of a new multicultural and interethnic formation.